Reconciling the Dual Legal Nature of Promissory Notes in Indonesian Default Disputes: A Normative Analysis of Supreme Court Ratio Decidendi (2001–2022) - Yoga Prasetyan; Fikri Hadi (Golden Ratio of Law and Social Policy Review, 2026)
A promissory note constitutes an unconditional written promise by the issuer (maker) to pay a specified sum to the holder (payee) at an agreed time. Although its use in Indonesian corporate financing and cross-border transactions has grown, its legal standing in default (wanprestasi) disputes remains governed by overlapping and partly untested provisions of the Commercial Code (KUHD) and Civil Code (KUH Perdata). This study employs normative legal research using statutory, conceptual, case-based, and comparative approaches, examining eight Supreme Court and first-instance decisions issued between 2001 and 2022 and comparing them against Article 3 of the United States Uniform Commercial Code, the United Kingdom's Bills of Exchange Act 1882, and the Geneva Convention 1930. The analysis shows that a promissory note occupies a dual legal position as a negotiable instrument under KUHD Articles 174–177 and as a contractual instrument under the KUH Perdata and identifies three recurring jurisprudential inconsistencies: inconsistent application of the abstraction principle, variable tolerance for formal defects, and unsettled criteria for what constitutes sufficient notice of default. These findings indicate that judicial guidance, rather than case-by-case adjudication alone, is needed to stabilize this area of commercial law. The study recommends that the Supreme Court issue a circular letter (SEMA) or regulation (PERMA) through its Civil Chamber plenary meeting to unify these standards, alongside legislative reform of the KUHD's negotiable-instrument provisions.